Réponses

2014-09-20T23:43:53+02:00
Ex.43:
G(x)= \frac{-5}{2x^{2}-3}

1)a)G(-1)= \frac{-5}{2*(-1)^{2}-3}
= \frac{-5}{2-3}
= \frac{-5}{-1}
=5
   
   b)G(0)=
 \frac{-5}{2*0^{2}-3}
= \frac{-5}{2*0-3}
= \frac{-5}{-3}
= \frac{5}{3}
   
   c)G( \frac{5}{2} )= \frac{-5}{2* (\frac{5}{2})^{2}-3}
= \frac{-5}{\frac{25}{2}-3}
= \frac{-5}{\frac{25}{2}-3}
= \frac{-5}{\frac{19}{2}}
= \frac{-10}{19}

   d)G(2\sqrt{3} )= \frac{-5}{2(2\sqrt{3})^{2}-3}
= \frac{-5}{2*4*3-3}
= \frac{-5}{24-3}
= \frac{-5}{21}

2) \frac{-5}{2x^{2}-3} =2
 \frac{2x^{2}-3}{-5} = \frac{1}{2}
⇔2x^{2}-3= \frac{-5}{2}
⇔2x^{2}= \frac{-5}{2} +3
⇔2x^{2}= \frac{1}{2}
⇔x^{2}= \frac{1}{4}
⇔|x|= \frac{1}{2}
⇔x= \frac{1}{2} ou x= \frac{-1}{2}

3)oui 0 est un antécédent de G car G est définie ssi 2x^{2}-3≠0 et 2*(0)²-3=-3≠0

4) D_{f(G)}={x∈R tq 2x^{2}-3≠0}
2x^{2}-3≠0
⇔2x^{2}≠3
⇔x^{2}≠ \frac{3}{2}
⇔|x|≠ \frac{\sqrt{3}}{\sqrt{2}}
⇔x≠ \frac{\sqrt{3}}{\sqrt{2}} ou x≠ \frac{-\sqrt{3}}{\sqrt{2}}
 D_{f(G)}=R'{ \frac{\sqrt{3}}{\sqrt{2}}  \frac{-\sqrt{3}}{\sqrt{2}} }
d'où  \frac{\sqrt{3}}{\sqrt{2}} et  \frac{-\sqrt{3}}{\sqrt{2}} sont les nombres qui n'ont pas d'images par G